If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (3x + -5) + (2x) = 90 Reorder the terms: (-5 + 3x) + (2x) = 90 Remove parenthesis around (-5 + 3x) -5 + 3x + (2x) = 90 Combine like terms: 3x + (2x) = 5x -5 + 5x = 90 Solving -5 + 5x = 90 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '5' to each side of the equation. -5 + 5 + 5x = 90 + 5 Combine like terms: -5 + 5 = 0 0 + 5x = 90 + 5 5x = 90 + 5 Combine like terms: 90 + 5 = 95 5x = 95 Divide each side by '5'. x = 19 Simplifying x = 19
| 3x+8=8x | | x+6x+12-20=180 | | 16=3x+4 | | 9x+11-(10-x)=-9 | | (t-5)(t-2)= | | 18p-13+12p=72p-3-24p | | 6r^2+7r+5=0 | | (-3+2i)+(5-6i)= | | x+4+3x=8 | | 5x+4=x+32 | | (21+7)-16/2+3*5= | | -7x-10=46 | | 5x-7=-10x+9 | | 450=1200-3(t) | | 2(z+1)-3=z-3 | | 3.2+x=7.5 | | x^3+6x^2-5x=0 | | -9r=u | | x(3x-9)=0 | | 1x+4=-2 | | 21+7-16/2+3*5= | | 6-3x=10-5x | | x+3/8=-1/4 | | 6x+12=11-33 | | 0=16x^2-26x+7 | | 3(x+9)=48 | | -113=5x+-2(7x+25) | | 1s+-3=-6 | | (1/2)x+16=(2/3)x-4 | | 450=1200-3t | | x*2-12=44 | | 4ab-3ab^2= |